Project Based Learning: Peningkatan Hasil Belajar Peserta Didik pada Materi Jenis Wiwaha Menggunakan Media Canva di SMA Negeri 1 Basarang - KT. Maryani Anjasmari (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2023)
This study aims to improve the learning outcomes of students on wiwaha type material through a project based learning (PjBL) model with Canva media. This research design uses a quasi-experimental research design (pseudo-experiment). The population in this study was all grade XI students of SMAN 1 Basarang, while the sample was grade XI-1 students. Data was collected through observation and provision of test questions in the form of pre-test and post-test questions. Data analysis techniques use quantitative data analysis. From the results of the study, student learning results were obtained on the wiwaha type material after being taught using a PjBL model using Canva media, a percentage of 100% of students achieved KKM scores. The increase in student learning outcomes is in line with the increase in student activity with a percentage of 85%. Thus, the PjBL model with Canva media is able to improve student learning outcomes on wiwaha type material, also having a positive impact on student activities.